2020
DOI: 10.1097/jsm.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Human Leukocyte Antigen Antibody Formation After Distal Tibia Allograft and Subsequent Graft Resorption

Abstract: The association between donor-specific human leukocyte antigen (HLA) antibody formation and small bone allograft resorption has not been studied. We present the case of a patient treated for glenoid bone loss using a distal tibial allograft with Bankart repair who formed donor-specific HLA antibodies against the allograft and had subsequent graft resorption. X-ray and computed tomography (CT) scans were performed before and after surgery at standard checkpoints. Patient blood and serum samples were collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Our results elaborate on the findings presented by Liwski et al 5 and O’Sullivan et al 7 regarding postoperative sensitization to donor HLA in the context of small bone allografts. Notably, the case presented by Liwski et al showed evidence of sensitization against donor Class I and Class II HLA.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results elaborate on the findings presented by Liwski et al 5 and O’Sullivan et al 7 regarding postoperative sensitization to donor HLA in the context of small bone allografts. Notably, the case presented by Liwski et al showed evidence of sensitization against donor Class I and Class II HLA.…”
Section: Discussionsupporting
confidence: 90%
“… 3 , 6 , 7 , 12 , 14 , 16 , 17 However, 2 recent case studies have provided evidence of development of donor-specific HLA antibodies after small bone allografting procedures. 5 , 7 Both cases highlight the potential risks of HLA sensitization after elective surgery, particularly in the case presented by O’Sullivan et al 7 regarding a patient who was placed on a deceased donor waitlist for renal transplant after the sensitization event. Importantly, the case study presented by Liwski et al 5 suggests a possible relationship between postoperative sensitization against donor HLA and resorption.…”
mentioning
confidence: 98%
See 3 more Smart Citations